Identifikasi Tumbuhan Mangrove di Hutan Lindung Padu Empat-Lebak Kerawang Desa Batu Ampar Kabupaten Kubu Raya - Maryam, Siti; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Mangroves in Batu Ampar Village, West Kalimantan Province are under threat of damage because they are used as various commercial purposes by the local community such as logging mangrove trees for the mangrove charcoal industry. Mangroves have a vital functions for the environment, so that mangrove conservation is necessary. One of the mangrove conservation efforts is to know the types of mangrove plants in an area. The purpose of this study was to identify the types of mangrove plants and categorize into major, minor and associated mangroves found in the Padu Empat-Lebak Kerawang Protection Forest, Batu Ampar Village, West Kalimantan. Data collection used a survey method with a zig-zag cruising technique. There were 3 routes used in this research. The herbarium was made to facilitate the identification of mangrove plants. The identification results showed that there were 7 species of mangrove which included in 5 families: Rhizophoraceae, Arecaceae, Meliaceae, Pteridaceae, and Moraceae. The seven species found were divided into 3 mangrove groups, namely 4 major mangroves including Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, and Nypa fruticans; 2 minor mangroves including Xylocarpus granatum and Acrostichum speciosum, and 1 associated mangrove, namely Ficus retusa.